Ethnobotanical survey of medicinal plants utilized for treating skin inflammation in the Robertson area, Western Cape, South Africa. - Nhlahla Cecil Mitileni; Singh, Karishma (Student's Journal of Health Research Africa, 2026)
Background Skin inflammation remains a common dermatological condition affecting quality of life globally. In many South African communities, traditional medicine continues to serve as a primary healthcare resource. This study documents medicinal plants used for treating skin inflammation in the Robertson area of the Western Cape and evaluates associated ethnobotanical knowledge. Methods A qualitative ethnobotanical survey was conducted between March and June 2024 in Robertson, Western Cape. Thirty informants (28 males and 2 females) aged 18 years and above were selected through purposive and snowball sampling. Semi-structured interviews, which were pilot-tested before data collection, were conducted and lasted approximately 30–60 minutes. Data collected included plant species used, parts utilized, preparation methods, dosage, growth habits, and socio-demographic characteristics. Ethical clearance was granted by the Mangosuthu University of Technology Research Ethics Committee (REF: RD5/59/2024; approved 15 February 2024). Results A total of 30 plant species belonging to 22 families were documented. The dominant families were Asphodelaceae and Asteraceae (n = 3 each). Shrubs constituted the highest growth habit category (43.33%), followed by herbaceous plants (16.67%). Leaves were the most utilized plant part (60.98%). Infusion (35.14%) was the most frequently reported preparation method, followed by decoction and poultice (18.92% each). Aloe ferox, Bulbine frutescens, Centella asiatica, and Gomphocarpus fruticosus were the most cited species. Conclusion The findings illustrate the rich tradition of herbal medicine in the Robertson region and highlight the cultural significance of these indigenous plants in traditional therapeutic practices, emphasizing the need for conservation and further research on these species. Recommendation Preservation of this knowledge and conservation of plant species are crucial.